Managing nuclear operations - Carter, Ashton B.; Steinbruner, John D.; Zraket, Charles A.; Brookings Institution; John F. Kennedy School of Government (Washington, D.C. : Brookings Institution, 1987)
This book analysed the dynamics of nuclear operations and the viral policy problems they pose.
A study jointly sponsored by the Brookings Institution and the Center for Science and International Affairs at Harvard University.
Includes bibliographical references and index.
asm 21/01/19
Loans
Keywords: Nuclear warfare